ANALISIS PROFITABILITAS USAHA TERNAK SAPI POTONG DI KECAMATAN AMARASI KABUPATEN KUPANG - Kristian Dangu Uba; Melkianus Tiro; Solvi Mariana Makandolu (Universitas Nusa Cendana, 2015)
A study using survey method was conducted in the District of Amarasi, Regency of Kupang. The study aimed to : 1) Identify and analyze the profitability of beef cattle farm in the district of Amarasi, Regency of Kupang , and 2) Evaluate and analyze the efficiency of production factors used in beef cattle farm in the District of Amarasi, Regency of Kupang. Sampling was conducted in 2 stages. The first: selecting 5 villages purposively based on the criteria of having the largest beef cattle population. The second: selecting 60 farmers from the 5 selected villages by applying simple random sampling. Data were analyzed using input output analysis, profitability analysis, as reflected by the value of Gross Profit Margin (GPM), Net Profit Margin (NPM), and Operating Profit Margin (OPM) and correlation – regression analysis. Technical efficiency of using production factors in beef cattle farm can be determined from Σbi obtained while economic efficiency can be measured by looking at the ratio of the value of marginal product and marginal factor costs. Data were analyzed using the program of Microsoft Office Excel 2007. The results showed that the profit obtained from beef cattle production was Rp. 12,823,688/year. Further, the profitability is as follows: GPM = 94.07%; NPM = 79.96%; and OPM = 94.07%. Results of regression analysis showed an equation as follow: Y = 11,20 X12,22X21,29X3-2,83X40,07 (R2 = 0.70). Factors that affect the income of beef cattle production were: the number of livestock raised, feed costs, veterinary costs and the cost of the rope. Both technical and economic analyze showed that the use of production factors in the beef cattle production at the Amarasi District – Regency of Kupang were efficient which indicated by Σbi <1 (Σbi = 0.75) and the ratio of Marginal Product Value and Marginal Factor Cost >1 (MPV/MFC = 9.154). Therefore, it is recommended that business reorganization needed to achieve the both technical and economic efficiency. ABSTRAK Tujuan penelitian ini adalah : 1) mengidentifikasi dan menganalisis tingkat profitabilitas dari usaha ternak sapi potong di Kecamatan Amarasi Kabupaten Kupang, dan 2) mengetahui dan menganalisis efisiensi penggunaan faktor-faktor produksi pada usaha ternak sapi potong di Kecamatan Amarasi Kabupaten Kupang. Pengambilan contoh dilakukan dalam dua tahap. Tahap pertama penentuan Desa Contoh yang dilakukan secara purposif sebanyak lima desa dengan pertimbangan bahwa memiliki populasi ternak sapi terbanyak. Tahap kedua adalah menentukan 60 peternak secara acak sederhana dari desa-desa terpilih. Data dianalisis dengan menggunakan analisis input output, analisis profitabilitas yang dicerminkan oleh nilai Gros Profit Margin (GPM), Net Profit Margin (NPM), dan Operating Profit Margin (OPM) dan analisis korelasi – regresi. Efisiensi teknis penggunaan faktor-faktor produksi pada usaha ternak sapi potong dapat dilihat dari ∑bi yang diperoleh sedangkan efisiensi ekonomis dapat diukur dengan melihat ratio nilai produk marginal dan biaya faktor marginal. Seluruh data dianalisis dengan menggunakan Program Microsoft Office Excel 2007. Hasil penelitian menunjukkan bahwa usaha ternak sapi potong mampu menghasilkan laba sebesar Rp. 12,823,688/tahun. Profitabilitas usaha ini ditunjukkan oleh GPM = 94,07 %; NPM = 79,96%; dan OPM = 94,07%. Hasil analisis regresi diperoleh persamaan regresi: Y= 11,20X12,22X21,29X3-2,83X40,07( R2 = 0,70). Faktor yang berpengaruh terhadap pendapatan pada usaha ternak sapi potong adalah jumlah kepemilikan ternak, biaya pakan, biaya kesehatan dan biaya tali pengikat. Secara teknis dan ekonomis penggunaan faktor – faktor produksi pada usaha ternak sapi potong di Kecamatan Amarasi Kabupaten Kupang berada pada daerah efisien terlihat dari ∑bi > 1 (∑bi = 0,75) dan nilai NPMXI/PXI<1 ( NPMXI//PXI = 9,154). Oleh karena itu perlu dilakukan reorganisasi usaha untuk mencapai efisiensi dimaksud.